Mobile-Health Tool Use and Community Health Worker Performance in the Kenyan Context: A Quasi-Experimental Post-Test Perspective - Gatara, Maradona (Journal of Health Informatics in Africa, 2015)
Background and Purpose: Community Health Workers (CHW’s) are often the only link to healthcare for millions of people in the developing world. Mobile-health or ‘mHealth’ tools can support CHWs in monitoring and evaluation, disease surveillance, and point-of-care diagnostics. However, there is a lack of evidence on the impacts of mHealth on CHW performance. To address this gap, we determine a set of measures along which to evaluate the impact of mHealth tools on CHW performance. Methods: Using a quasi-experimental post-test design we compare CHWs using an mHealth tool (n=196) with those using a paper-based system (n=199). The empirical context for the study is peri-urban communities in Kenya and data was collected using a survey instrument. Results: Results provide evidence of impacts of mHealth tool use on objective and perceptual performance measures. Conclusions: CHWs using mHealth tools capture and transmit higher percentages of monthly cases on time and without missing data, and are highly satisfied with the contribution of the tool to their performance.